The effects of individual and organizational interventions on space tourism: applying EMGB and fsQCA. Issue 9 (3rd May 2023) - Kim, Myung Ja; Hall, C. Michael; Kwon, Ohbyung; Sohn, Kwonsang; Kim, Minseong
ABSTRACT: There is limited theoretically informed research on sustainability in the space tourism market. An extended model of goal-directed behaviour (EMGB) is created and verified with individual and organizational interventions, comparing space tourism experienced and non-experienced travellers. Results revealed that individual intervention has fully significant effects on all MGB constructs, while organizational intervention has partially significant impacts, which in turn influence desire relevant to behavioural intention. The findings from fsQCA showed the different profiles of experienced and non-experienced tourists.